Implementing lean manufacturing in Malaysian small and medium startup pharmaceutical company - Wan Ibrahim, Wan Mohd Khairi; Abdul Rahman, Mohamed; Abu Bakar, Mohd Rushdi (IOP Publishing, 2017)
Domestic pharmaceutical industry has been identified by the Malaysian government as an industry to be developed under its 11th economic development plan. Most homegrown pharmaceutical companies fall under the category of small and medium enterprises (SME) and therefore need to be highly efficient in their operations to compete with the multinationals. Though lean manufacturing is a well-known methodology to achieve an efficient operation, only a small percentage of the local SMEs implement it. The study aims to determine the real success factors in lean implementation through systematic review of relevant literature on lean manufacturing implementation in local companies, onsite observation of a selected SME company, Global Factor Sdn. Bhd. (GFSB), that successfully implemented lean manufacturing followed by actual implementation of lean project at IKOP Sdn. Bhd., a small startup pharmaceutical company. Lean tools like Gemba, value stream map (VSM) and spaghetti diagram were used to analyze and improve a process at IKOP Sdn. Bhd. The literature review showed that the implementation of lean manufacturing at Malaysian SMEs involved in pharmaceutical industry is at its infancy. Study at GFSB indicated that successful implementation of lean manufacturing stems from management support, employee’s commitment, government support and knowledge on lean among employees. Application of lean tools in IKOP Sdn. Bhd. to improve the process cycle efficiency of hand sanitizer, i-Hand 4.0, has shown that the GMP guidelines are not jeopardized. The Kaizen improvement project resulted in 46.3% reduction in lead time. It may be concluded that implementing lean manufacturing in any small local startup pharmaceutical company is beneficial in reducing operational costs and increasing the efficiency and effectiveness and does not conflict with the existing GMP guidelines.